Circulating galectin-3 promotes tumor-endothelium-adhesion by upregulating ICAM-1 in endothelium-derived extracellular vesicles - Wang, Lei; Du, Dan-Dan; Zheng, Zong-Xue; Shang, Peng-Fei; Yang, Xiao-Xia; Sun, Chao; Wang, Xiao-Yan; Tang, Ya-Jie; Guo, Xiu-Li (Frontiers in Pharmacology, 2022)
The adhesion of tumor cells to vascular endothelial cells is an important process of tumor metastasis. Studies have shown that tumor could educate vascular endothelial cells to promote tumor metastasis through many ways. However, the effect of tumor cells on the functions of vascular endothelial cells-derived extracellular vesicles (H-EVs) and the mechanisms underlying their effects in tumor-endothelium adhesion in metastasis remain mysterious. In this study, we found that H-EVs promoted the adhesion of triple negative breast cancer cell to endothelial cells and cirGal-3 enhanced the adhesion-promoting effects of H-EVs. The underlying mechanism was related to the upregulation of glycolysis in endothelial cells induced by cirGal-3 which led to the increase of the ICAM-1 expression and its transmission to MDA-MB-231 cells by H-EVs. Targeting of cirGal-3 or glycolysis of vascular endothelium in breast cancer therefore represents a promising therapeutic strategy to reduce metastasis.